Ontogenesis of stomata in Velloziaceae: paracytic versus tetracytic? - Amaral,Marina Milanello do (2008)
In Velloziaceae, the number of subsidiary cells has been used to characterize species and support groups. Nevertheless, the homology of the stomatal types have not been scrutinized. Stomatal ontogenesis of Vellozia epidendroides and V. plicata, assigned to have tetracytic stomata, and of V. glauca and Barbacenia riparia, assigned to have paracytic stomata, were investigated. In the four species studied, stomata followed perigenic development. Subsidiary cells arise from oblique divisions of neighbouring cells of the guard mother cell (GMC). These cells are elongated and parallel to the longer axis of the stoma. Polar cells show wide variation, following the shape and size of the epidermal cells in the vicinity. Hence, these cells cannot be called subsidiary cells. This wide variation is due to a much higher density of stomata in some regions of the leaf blade. This distribution of stomata forces the development of short polar cells, leading to an apparently tetracytic stomata. In regions of low concentration of stomata, higher spatial availability between the GMCs allows the elongation of polar cells, leading to evident paracytic stomata. Therefore, the four studied species are considered braquiparacytic, questioning the classification of stomata into tetracytic and paracytic in Velloziaceae.